ANALISIS KRITERIA PEMILIHAN METODE KONSTRUKSI CAPPING BEAM TANGGUL PENGAMAN PANTAI NCICD JAKARTA UTARA - Norita, Khansa; Saputra, Pungky Dharma; Z, Yanda Dwira Firman (Politeknik Negeri Jakarta, 2025)
The annual flooding that affects the capital city of the Republic of Indonesia is a critical issue being addressed through solutions outlined in the NCICD (National Capital Integrated Coastal Development) master plan. The capping beam, which forms the upper structure of the embankment, breaks waves, unites the spun pile series, and maintains the stability of the spun pile. The main objective of this study is to identify the criteria for selecting the capping beam construction method in the NCICD coastal protection embankment development project. The method used is a systematic approach to literature published in the form of articles or journals and scientific publications. The results of the study show that there are nine criteria for selecting the method of capping beam construction. The criteria that are widely discussed and have a dominant influence are the cost criteria and environmental conditions, with each having a percentage of 19%. This study provides valuable insights for academics and practitioners in developing effective strategies for construction method selection.